PERANCANGAN LOGO REGIONAL WORKSHOP WORLD OCEAN ASSESSMENT BELITUNG - Valentina, Anny; Elysia, Celine; Aurellia, Meysia Dewi; Natassya, Amelia (Jurnal Serina Abdimas, 2023)
WOA 2022 is the second international agenda in Belitung Regency after the implementation of the G20 Development Working Group (DWG) in September. The World Ocean Assessment (WOA) is a world maritime meeting that focuses on discussing issues of the marine environment and their social and economic effects. Belitung was chosen because it has sea that still preserved from all kinds activities that can damage the conservation. Considering that the WOA event will be held in December 2022 and is an international event, to welcoming this event the local government needs help from professionals to design a logo event. As a very important visual identity, logo is the main face of a brand and has a meaning that can explain the vision or purpose of the brand. Implementing the method of this PKM, in the first stage communication was carried out with the Belitung Regency Regional Government. Through Deputy Regent Isyak Meirobie, the PKM DKV Untar team was invited to collaborate. The second stage is literature study, observation with visual design that supports the spirit of 'Let's Go Belitung'. Then find a solution to the problem by processing the icons from Belitung into a visualization that is manifested into a logo. In the fifth stage, a visual design is made by applying the Belitung icons to the logo and providing several visual alternatives and making revisions if necessary. In the end, a logo was sent which was then applied to Instagram @kemenkomarves. WOA 2022 menjadi agenda internasional kedua di Kabupaten Belitung setelah pelaksanaan Development Working Group (DWG) G20 pada bulan September. World Ocean Assessment (WOA) adalah pertemuan maritim dunia yang berfokus membahas isu-isu lingkungan laut dan efeknya terhadap sosial dan ekonomi. Belitung dipilih karena memiliki laut yang masih terjaga kelestarian dari segala macam kegiatan lain yang dapat merusak pelestarian. Mengingat acara WOA akan dilaksanakan pada bulan Desember 2022 dan merupakan acara internasional, maka Pemda membutuhkan bantuan tenaga professional untuk merancang logo event untuk menyambut berlangsungnya event ini di Belitung. Sebagai identitas visual yang sangat penting, logo merupakan wajah utama dari sebuah brand dan tentunya memiliki makna yang dapat menjelaskan visi atau tujuan dari brand tersebut. Metode pelaksanaan PKM, pada tahap pertama dilakukan komunikasi dengan pihak Pemda Kabupaten Belitung. Melaui Wakil Bupati Isyak Meirobie diajaklah tim PKM DKV Untar untuk berkolaborasi. Tahap kedua studi pustaka, observasi dengan perancangan visual yang mendukung agar sesuai dengan spirit ‘Let’s Go Belitung”. Lalu mencari solusi dari permasalahan dengan mengolah ikon-ikon dari Belitung menjadi visualisasi yang diwujudkan menjadi logo. Pada tahap ke lima dibuat rancangan visual dengan mengaplikasikan ikon-ikon Belitung kedalam logo dan memberikan beberapa alternatif visual serta membuat revisi jika diperlukan. Pada akhir dikirimkan logo yang kemudia telah diaplikasikan pada Instagram @kemenkomarves.